تأثير وسائل لعبة صيد المفردات في ترقية المفردات العربية لطلاب الفصل السابع بمدرسة معلمين نهضة الوطن فنشور المتوسطة الدينية الإسلامية - Sya’ban Nurhikmah; Idiatussaufiah, Idiatussaufiah; Asriandi, Asriandi (Lughatu Ad-dhat, 2024)
Arabic is one of the subjects that requires the teacher's ability to manage the class. Learning Arabic is still less popular and often observing learning makes students bored so that Arabic is considered difficult, therefore we need a method that can arouse students' interest in learning, one of which is the word hunting game.The aims of this research are: (1) to determine the application of the word hunting game in learning Arabic for class VII MTs Mualimin NWDI Pancor, (2) to determine the influence of the word hunting game media in increasing the Arabic vocabulary for class VII MTs Mualimin NWDI Pancor. The research method used is quantitative research and experimental methods with Pret-Test and Post-Test. The result of the Pret-Test score for the experimental class was 68.67, the Pret-Test for the Control class was 52.83 and the post-Test score for the experimental class was 78.17, the control class was 72.00, while the T-Test results showed that T-count > T-table (2.584 > 2.002) , then Ha is accepted and Ho is rejected, so from these results it can be concluded that the use of word hunting game media has an influence in increasing Arabic vocabulary at MTs Mualimin NWDI Pancor.